Video analysis of vehicular flows for road traffic monitoring - Ong, Kai Sin. (2009)
Video Analysis of Vehicular Flows for Road Traffic Monitoring” is a final year project that aims to develop a real time computer vision system that can collect traffic data, detect traffic incidents and has practical applications on intelligent traffic monitoring. Videos are sourced from Land Transport Authority (LTA) and the objectives of this project is to create a program that can detect traffic events through streaming from the IP network camera and alert the end user on the traffic conditions on the particular highway.